Measurement of the forces on ball in flight using built-in accelerometer - Koyanagi, R.; Ohgi, Y. (The Engineering of sport 7, Volume 2, 2008)
In this study, tri-axial accelerometer was installed in a ball to measure the aerodynamic forces during the ball's flight. The control experiments to validate were conducted besides the pitching experiment, to examine ball linear or angular velocity components independently. These were performed using a turntable and free fall lest, respectively. The acceleration data of the throwing experiment showed a semi-sinusoidal wave pattern. On the other hand, this wave pattern was not observed in the acceleration data of both the rotational table experiment and free-fall experiment. It was revealed (hat the change of the orientation vectors of the gravitational acceleration and the translation acceleration on the sensor coordinate System caused the sinusoidal acceleration pattern.